Eltrombopag for advanced myelodysplastic syndromes or acute myeloid leukaemia and severe thrombocytopenia (ASPIRE): a randomised, placebo-controlled, phase 2 trial. Issue 1 (January 2018) - Mittelman, Moshe; Platzbecker, Uwe; Afanasyev, Boris; Grosicki, Sebastian; Wong, Raymond S M; Anagnostopoulos, Achilles; Brenner, Benjamin; Denzlinger, Claudio; Rossi, Giuseppe; Nagler, Arnon; Garcia-Delgado, Regina; Portella, Maria Socorro O; et al.
Summary: Background: Thrombocytopenia is a life-threatening complication in patients with advanced myelodysplastic syndromes (MDS) and acute myeloid leukaemia (AML). In this study (ASPIRE), we aimed to assess eltrombopag, an oral thrombopoietin receptor agonist, for thrombocytopenia (grade 4) treatment in adult patients with advanced MDS or AML. Methods: ASPIRE consisted of an open-label, double-blind phase for 8 weeks and a randomised, double-blind phase (parts 1 and 2, reported here) for 12 weeks, and an open-label extension (part 3). Eligible patients were men and women aged 18 years or older, with intermediate-2 or high-risk MDS or AML, with bone marrow blasts of 50% or less, and had either grade 4 thrombocytopenia due to bone marrow insufficiency (platelet counts <25 × 10 9 per L) or grade 4 thrombocytopenia before platelet transfusion, with 25 × 10 9 platelets per L or greater after transfusion. Additionally, eligible patients had at least one of the following within the screening period of 4 weeks: platelet transfusion, symptomatic bleeding, or platelet count of less than 10 × 10 9 per L. During part 1, patients received eltrombopag, and dose-escalation criteria for part 2 were determined. In part 2, we randomly allocated patients 2:1 using an interactive voice-response system to eltrombopag or placebo, stratified by baseline platelet count (<10 × 10 9 platelets per L vs ≥10 × 10 9 platelets per L) and disease (MDS vs AML). In parts 1 and 2, patients received supportive standard of care and initiated eltrombopag or placebo at 100 mg per day (50 mg per day for patients of east-Asian heritage) to a maximum of 300 mg per day (150 mg per day for patients of east-Asian heritage). The part 2 primary objective was assessed by a composite primary endpoint of clinically relevant thrombocytopenic events (CRTE) during weeks 5–12, defined as one of the following events, either alone or in combination: grade 3 or worse haemorrhagic adverse events; platelet counts of less than 10 × 10 9 per L; or platelet transfusions. Efficacy analyses were based on intention to treat; clinically meaningful efficacy was defined as 30% absolute difference between groups. This trial is registered withClinicalTrials.gov, numberNCT01440374 . Findings: In part 1, 17 patients received eltrombopag and 11 patients completed treatment; four experienced significantly increased platelet counts, and ten had reduced platelet transfusion requirements. In part 2 we randomly allocated 145 patients to receive supportive care plus eltrombopag (n=98) or placebo (n=47); similar proportions had MDS (50 [51%] patients to eltrombopag, 22 (47%) patients to placebo) or AML (48 [49%] patients to eltrombopag, 25 [53%] patients to placebo). Average weekly CRTE proportions from weeks 5–12 were significantly lower with eltrombopag (54% [95% CI 43–64]) than with placebo (69% [57–80], odds ratio [OR] 0·20, 95% CI 0·05–0·87; p=0·032) although the difference between treatment groups was less than 30%. The most common grade 3 and grade 4 adverse events were fatigue (six [6%] in the eltrombopag group and one [2%] in the placebo group), hypokalaemia (six [6%] and two [4%]), pneumonia (five [5%] and five [11%]), and febrile neutropenia (five [5%] and six [13%]). Serious adverse events were reported in 56 (58%) eltrombopag-treated patients and 32 (68%) placebo-treated patients. Seven eltrombopag recipients and two placebo recipients had serious adverse events that were suspected to be study drug-related (eltrombopag: acute kidney injury, arterial thrombosis, bone pain, diarrhoea, myocardial infarction, pyrexia, retinal vein occlusion, n=1 each; placebo: vomiting, white blood cell count increased, n=1 each). Two eltrombopag recipients (arterial thrombosis n=1; myocardial infarction n=1) and no placebo recipients experienced fatal serious adverse events suspected to be study drug-related. Interpretation: No new safety concerns were noted with eltrombopag and the trial met the primary objective of a reduction in CRTEs; eltrombopag might be a treatment option for thrombocytopenic patients with AML or MDS who are ineligible for other treatment and who are not receiving disease-modifying treatment. Funding: Novartis Pharma AG.